Nutrition management for patients with head and neck cancer during peri-radiotherapy: A systematic review and quality appraisal of clinical practice guidelines using the AGREE II instrument - Zhao, Jing; Kan, Yajing; Wu, Xueting; Yang, Shuang; Wang, Guozhou; Bao, Yuting; Li, Jing (Frontiers in Oncology, 2022)
Objective To evaluate the quality of clinical practice guidelines (CPGs) for nutrition management of patients with head and neck cancer (HNC) during peri-radiotherapy, as well as to summarize the nutrition recommendations fitting the subject. Methods CPGs published in English, Chinese and German were identified from databases, guideline networks, and websites of nutritional associations from the databases’ inception to March 8, 2022. Three independent appraisers used the Appraisal of Guidelines for Research and Evaluation II (AGREE II) Instrument to assess the quality of CPGs. The intraclass correlation coefficient (ICC) was used to calculate appraiser agreement. Results 769 records were identified. After removing duplicates, 470 articles were screened. 12 CPGs were identified with nutrition-specific recommendations. 67% of CPGs were rated as high quality, and 33% as low quality. Recommendations were categorized into nutritional risk screening, nutrition assessment, nutrition counseling, nutrition interventions, nutrition intake, swallowing function management, weight management, exercise, multidisciplinary team, post-discharge care, nutrients, and pharmacologic interventions. Conclusion We found discrepant recommendations in existing CPGs, including nutrition screening, nutrition assessment, nutrition intake, and nutrients. We also reported the absence of essential parts of CPGs, including the views of its target users, the statement of external review, and the method to formulate the recommendations, strategies to improve uptake, and resource implications of applying the CPGs. CPGs with low quality should be improved in future updates based on currently available guideline development tools. Specialized CPGs on nutrition management for HNC patients during peri-radiotherapy should be developed.